Determination of the Variation of Nitrogen Pressure on the Surface Hardness Obtained by Nitriding Steel in Plasma Focus Devics - Ng, Xue Yinn (2017)
A 3kJ Mather-type plasma focus device used to carry out plasma nitriding on the surface of AISI 1020 carbon steel. The nitriding process was carried out under different nitrogen gas pressure (0.5, 1.0, 1.5 and 2.0 Torr) and different axial distance of steel from anode tip (40, 60, 80, 100, 120mm). The surface hardness and surface morphology of the nitrided steel were studied through the observation by using Vickers hardness tester and optical microscopy respectively. Lee Model Code was used to measure the dynamic of ion beam emitted by plasma focus device to identify the parameters of ion beam, in term of ion beam energy, ion current and number of ion per shot. The results of ion beam parameters were correlated with the surface hardness of nitrided steel to study their relationships. Efficient nitriding occurred at the operation with 1.0 Torr of nitrogen gas which steel was placed 40mm above anode tip. A thin non-homogenous layer of shiny white colour iron nitrided with 10-30mm diameter was formed on the surface of nitrided steel which indicated that sputtering of steel cause by fast ion beam. The highest average surface hardness at epicentre was found to be 389.5 HV 0.2 with 125.5% of increment that its original value for the steel that treated with 1.0 Torr of nitrogen gas which the steel was placed 40mm above anode tip. Due to the fluctuation of the value of surface hardness, the average for the highest surface hardness was calculated and found to be 404.8 HV 0.2 with 134.4% of increment for the same sample. The correlation by using Lee Model Code showed that ion beam energy and ion beam energy and ion current had their peak value with 16.51J and 27.5kA respectively at the sample with highest surfaces hardness. The highest number of ions per shot occurred at the nitriding with 1.5 Torr nitrogen gas at 40mm axially above anode tip.